Groundwater contaminated by nitrates- a case study of Ado-Ekiti, Ekiti state, southwestern Nigeria (2012)
"Nitrate is one of the problematic and wide spread contaminations. Indiscriminate disposition of human and animal wastes in Nigeria especially in urban region, and lack of proper environmental sanitation geared the need for the monitoring of groundwater contamination. This research work monitored the concentration of nitrate and nitrate-nitrogen in portable water from wells in Odo Ado, Ado-Ekiti, Ekiti State, and examined the relationship between this concentration and the well depth as well as its nature (ringing). The results showed that out of 20 water wells sampled, 50% of samples contain high level of nitrate with the highest having concentration of 140 mg/L and least 49 mg/L while the remaining has acceptable concentration ranging between 3.5 mg/L and 35 mg/L with most ringed wells. The mean concentration of nitrates is 48.06 mg/L and the nitrate-nitrogen is 10.85 mg/L. The statistical correlation between the concentrations and depth showed that there is a significant difference between their means at 95% confidence using T-test. Out of ringed wells, five have high concentration and eight have low concentrations while two of the wells (not ringed) fall below the acceptable limit (EPA) which indicates that there are other factors such as closeness to the point source and soil texture which were not considered in this work. Key words: Nitrate, contamination, depth, groundwater, aquifer."